Особливості функціонування студентської періодики: від виникнення до сьогодення - Білограць, Христина; Bilograts, Christina; Билограць, Христина (Видавництво Львівської політехніки, 2017)
Проаналізовано історичні особливості української студентської періодики, описано соціально-політичні чинники, які впливали на її функціонування. Висвітлено проблеми сучасної преси для студентів. Подано порівняльну характеристику студентських видань минулого і сьогодення.

Analyzed the historical features of student periodicals in Ukraine, described the social and political factors. Specified the problems of modern media for students. Described the comparative characteristics of student press in the past and nowadays. After studying student press issues, it was discovered that censorship and funding are two major interconnected problems for young publishers. Problems that exist through funding can significantly change the editorial policy of student publications, linguistic peculiarities, and also influence the subject matter of published materials. The subject of publications in student publications is closely related to the events in society, in the past, students worried about what is going on around them and how global events will affect their lives. In the current issue of newspapers we can see articles on various topics, but when happens political events that may affect their future this is reflected in the publications. By searched for the reasons of the emergence and existence of the student press, we identified the various groups of publishers: future professionals (journalists, publishers and editors, philologists) and students studying on non-humanities. In most cases, they are driven by a desire to assert themselves, express their thoughts, and use a large amount of energy. Since the beginnings of the student periodicals and until now, it has been a long time, but in the newspapers that issued and issues, we can see a lot in common. The modern publications from the contemporary art and technical design, which has improved thanks to scientific and technological progress, are very different. There is also a significant the difference in the themes of articles. Because after independence in market conditions ideology and propaganda disappeared, publishers were doing their utmost to interest potential recipients, forgetting the importance of national education and ideology in the materials of student periodicals.

Проанализированы исторические особенности украинской студенческой периоди- ки, описаны социально-политические факторы, которые влияли на ее функциониро- вание. Освещены проблемы современной прессы для студентов. Дана сравнительная характеристика студенческих изданий прошлого и настоящего.
Features of functioning of the student periodic: from the beginning to the presentation
Особенности функционирования студенческой периодики: от возникновения до настоящего
Keywords: студентська періодика; газети та журнали; функціонування преси; student periodicals; newspapers and magazines; press functioning; студенческая периодика; газеты и журналы; функционирования прессы; 070.424